Nanocarbon‐based electrocatalysts for rechargeable aqueous Li/Zn‐air batteries - Wang, Ronghua (2020)
Rechargeable aqueous Li/Zn‐air batteries have become the most attractive energy storage devices because of their extremely high theoretical energy density, which enables electric vehicles to drive long range. However, current achievements still suffer from poor cycle life, low practical energy density, low round‐trip efficiency, and high manufacturing costs. One of the key challenges is the sluggish kinetics of oxygen electrochemistry during discharge and charge cycles. Thus, significant breakthroughs in design and synthesis of efficient electrocatalysts for the oxygen redox reaction are highly demanded. Nanocarbons, especially heteroatoms doped nanocarbons, are potential oxygen reduction reaction (ORR) catalysts due to the reasonable balance between catalytic activity, durability, and cost. Importantly, by introduction of transition metal nanoparticles, spinel oxides, layered‐double hydroxides, perovskite oxides, and other metal oxides, the constructed nanocarbon‐based materials could deliver promising bifunctional ORR and oxygen evolution reaction (OER) catalytic properties, which could be employed as air‐cathode materials to improve energy storage performances, even to get commercialized. Here, an overview of the recent progress of nanocarbon‐based electrocatalysts as air‐cathode materials for rechargeable aqueous Li/Zn‐air batteries is provided, aiming to highlight the benefits and issues of nanocarbon‐based electrocatalysts as well as to outline the most promising results and applications so far.